2023
DOI: 10.1177/08839115231207337
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and in vivo implantation of eugenol-loaded nanogels and PCL/Cs electrospun nanofibers for wound healing applications

Fariba Noori,
Mahmoud Osanloo,
Hamid Reza Moradi
et al.

Abstract: Developing wound dressings with a high potential to cover damaged skin tissue and facilitate cell adhesion and migration at the injury site is crucial in skin tissue engineering to accelerate wound healing. Electrospun nanofibers from natural/synthetic polymers are amongst the favorable wound dressings with appropriate physicochemical and biological properties. As well, nanoformulations of phenolic phytochemical “eugenol” have been shown to fasten wound healing via various anti-inflammatory and anti-oxidant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recently, nanogels containing essential oils or plant compounds have been widely used in animal models. For instance, nanogels containing cinnamon essential oil and eugenol showed promising effects in wound healing [ 73 , 74 ]. It seems that the achievements of such studies have reached enough maturity to measure their effectiveness in clinical trials, although their safety considerations must be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nanogels containing essential oils or plant compounds have been widely used in animal models. For instance, nanogels containing cinnamon essential oil and eugenol showed promising effects in wound healing [ 73 , 74 ]. It seems that the achievements of such studies have reached enough maturity to measure their effectiveness in clinical trials, although their safety considerations must be observed.…”
Section: Discussionmentioning
confidence: 99%